2018
DOI: 10.1002/jmri.26557
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between tumor glucose metabolism and multiparametric functional MRI (IVIM and R2*) metrics in cervical carcinoma: Evidence from integrated 18F‐FDG PET/MR

Abstract: Background Multiparameter, multimodality 18F‐FDG PET/MRI holds great potential for the diagnosis of cervical cancer based on the correlation between tumor glucose metabolism and imaging parameters. Purpose To characterize the heterogeneity of tumor glucose metabolism by evaluating the correlation between 18F‐FDG uptake parameters and multiparametric functional MRI metrics in cervical carcinoma. Study Type Retrospective. Population Fifty‐four patients with cervical carcinoma. Field Strength/Sequence Hybrid PET/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Perfusion-related IVIM-DWI parameters, such as D* and f, and the expression of angiogenic factors, such as VEGF, MMP-2, and MMP-9, in tumor tissue are significantly positively correlated with MVD (31,32,(37)(38)(39)(40)(41). IVIM-DWI parameters can be used to evaluate tumor angiogenesis (40,42,43). An IVIM-DWI study of a mouse lung cancer model showed that D* and f were positively correlated with VEGF expression (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perfusion-related IVIM-DWI parameters, such as D* and f, and the expression of angiogenic factors, such as VEGF, MMP-2, and MMP-9, in tumor tissue are significantly positively correlated with MVD (31,32,(37)(38)(39)(40)(41). IVIM-DWI parameters can be used to evaluate tumor angiogenesis (40,42,43). An IVIM-DWI study of a mouse lung cancer model showed that D* and f were positively correlated with VEGF expression (43).…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in the f values of colorectal cancer patients with different expression levels of mismatch repair proteins may be related to the differential expression of VEGF and its receptor, VEGFR2 (40). However, D* is reported to have no correlation with VEGF (42). The possible causes of these controversial findings may be that the structure and density of some capillaries cannot reflect the information from macroscopic tumors and blood vessels (42); other physiological processes, such as glandular secretion and fluid flows inside the glandular ducts and other ducts, may affect the measured D* values (45), and D* is associated with a low signal-to-noise ratio (46) and poor (C) MMP-9 (×200).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation